Bibliographie Liègeoise - Montjardin, Xavier De Theux de, (European History and Culture - Book Archive pre-2000., 1973)
Topo-bibliography of LiÃ¨ge (Luik, Belgium), comprising both books printed at LiÃ¨ge 1556-1885, and works about the ancient Principality and the actual Province. More than 15.000 (Besterman) entries.